Indictment: the criminal justice system on trial - Perrin, Benjamin (Aevo UTP, 2023)
"#MeToo. Black Lives Matter. Decriminalize Drugs. No More Stolen Sisters. Stop Stranger Attacks. Do we need more cops or to defund police? Harm reduction or treatment? Tougher sentences or prison abolition? The debate about Canada's criminal justice system has rarely been so polarized. This book brings the stories of survivors and offenders alike to the forefront to help us understand why the criminal justice system is facing such an existential crisis. Benjamin Perrin draws on his expertise as a lawyer, former top criminal justice advisor to the prime minister, and law clerk at the Supreme Court of Canada to investigate the criminal justice system itself. He critiques the system from a trauma-informed perspective, examining its treatment of victims of crime, Indigenous people and Black Canadians, people with substance use and mental health disorders, and people experiencing homelessness, poverty, and unemployment. Perrin also shares insights from others on the frontlines, including prosecutors and defence lawyers, police chiefs, Indigenous leaders, victim support workers, corrections officers, public health experts, gang outreach workers, prisoner and victims' rights advocates, criminologists, psychologists, and leading trauma experts. Bringing forward the voices of marginalized people, along with their stories of survival and resilience, Indictment shows that a better way is possible."--